Heavy Metals in Water and Sediment: A Case Study of Tembi River. (29th January 2014) - Shanbehzadeh, Saeed; Vahid Dastjerdi, Marzieh; Hassanzadeh, Akbar; Kiyanizadeh, Toba
Abstract : This study was carried out to examine heavy metals concentration in water and sediment of upstream and downstream of the entry of the sewage to the Tembi River, Iran. Samples were collected from upstream and downstream and were analyzed for Cd, Cr, Cu, Fe, Pb, Ni, and Zn by atomic absorption spectrophotometer. The results indicated that the average concentration of the metals in water and sediment on downstream was more than that of upstream. The comparison of the mean concentrations of heavy metals in water of the Tembi River with drinking water standards and those in the water used for agriculture suggests that the mean concentration of Cu and Zn lies within the standard range for drinking water and the mean concentration of Mn, Zn, and Pb lies within the standard range of agricultural water. The highest average concentration on downstream for Pb in water and for Mn in sediment was 1.95 and 820.5 ppm, respectively. Also, the lowest average concentration on upstream was identified for Cd in water and sediment 0.07 and 10 ppm, respectively. With regard to the results, it gets clear that using the water for recreational purposes, washing, and fishing is detrimental to human health and the environment.